The effects of cross‐linking a collagen‐elastin dermal template on scaffold bio‐stability and degradation. (28th July 2020) - Maitz, Joanneke; Wang, Yiwei; Fathi, Ali; Ximena Escobar, Francia; Parungao, Roxanne; van Zuijlen, Paul; Maitz, Peter; Li, Zhe
Abstract: MatriDerm is a collagen‐elastin dermal template that promotes regeneration in full‐thickness wound repair. Due to its noncross‐linked status, MatriDerm biodegrades quickly in a wound. Facilitating vascularization and dermal repair, it is desirable for MatriDerm to remain present until the wound healing process is complete, optimizing tissue regeneration and reducing wound contraction. The aim of this study was to investigate the effect of cross‐linking MatriDerm on its mechanical and biological properties and to enhance its regenerative functionality. MatriDerm was chemically cross‐linked and characterized in comparison with noncross‐linked MatriDerm. Scaffold properties including surface morphology, protein release and mechanical strength were assessed. Cell‐scaffold interaction, cell proliferation and migration were examined using human dermal fibroblasts. Scaffold biodegradation and its impact on wound healing and contraction were studied in a mouse model. Results showed that cross‐linked MatriDerm displayed a small reduction in pore size, significantly less protein loss and a threefold increase in tensile strength. A significant increase in fibroblast proliferation and migration was observed in cross‐linked MatriDerm with reduced scaffold contraction in vitro. In the mouse model, noncross‐linked MatriDerm was almost completely biodegraded after 14 days whereas cross‐linked MatriDerm remained intact. No significant difference in wound contraction was found between scaffolds. In conclusion, cross‐linked MatriDerm showed a significant increase in stability and strength, enhancing its durability and cell‐scaffold interaction. in vivo analysis showed cross‐linked MatriDerm had a reduced biodegradation rate with a similar host response. The extended structural integrity of cross‐linked MatriDerm could potentially facilitate improved skin tissue regeneration, promoting the formation of a more pliable scar.